2009
DOI: 10.1590/s0001-37652009000200003
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, botanical evaluation and screening of radical scavenging activity of collected pollen by the stingless bees Melipona rufiventris (Uruçu-amarela)

Abstract: Stingless bees in Brazil are indigenous and found all over the country. Bee pollen is used for its nutritional value in the human diet. It is made up of natural flower pollen mixed with nectar and bee secretions. In order to evaluate the chemical composition, free radical scavenging activity, and botanical origin, sample of pollen loads from stingless bee, Melipona rufiventris (Uruçu amarela) was studied. The EtOAc extract of pollen of Melipona rufiventris yielded the following compounds: p-hydroxycinnamic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 21 publications
3
35
1
2
Order By: Relevance
“…The IC50 of propolis extract for DPPH assay was 4.27 mg/ml. Specific pollen foraging activity and different diets of stingless bee itself may cause a difference in antioxidant activity [21][22].…”
Section: Figurementioning
confidence: 99%
“…The IC50 of propolis extract for DPPH assay was 4.27 mg/ml. Specific pollen foraging activity and different diets of stingless bee itself may cause a difference in antioxidant activity [21][22].…”
Section: Figurementioning
confidence: 99%
“…9 Kaempferol and quercetin can be used as markers for determining the quality of bee pollen, suggesting their potential role in prevention of free radical-implicated diseases such as cancer, cardiovascular diseases and also diabetes, among others. 10,11 Bee pollen has been shown to possess antimicrobial, 12,13 antifungal, 12,13 antioxidant, 11,13,14 anti-radiation, 15 hepatoprotective, 16,17 antiestrogenic, 18,19 antigenotoxic/antimutagenic, 13,18 anticancerogenic, 18 antiinflammatory, 13 and various anti-histopathologic capacities. 20 Pollen has been described as "nature's perfect food" for centuries and is a highly concentrated food source.…”
Section: Introductionmentioning
confidence: 99%
“…It has been successfully used for the treatment of some cases of benign prostatitis and for oral desensitization of children with pollen allergy (7). It has been reported that pollen has free radical scavenging activity (8).…”
Section: Introductionmentioning
confidence: 99%